PENCEGAHAN HOSPITALISASI BERULANG PENDERITA GAGAL JANTUNG KRONIK MELALUI PROGRAM EDUKASI DALAM RANGKA WORLD HEART FAILURE DAY DI RUANG TUNGGU POLIKLINIK JANTUNG RSUD TABANAN - I Putu Gede Eka Ariawan Ariawan Suyasa; IW Sutarmawan; RD Pratiwi; DAN Widari (JURNAL SEWAKA BHAKTI, 2023)
Chronic heart failure is a progressive syndrome that can reduce a person's quality of life and affect the economy and health. Risk factors for chronic heart failure are hypertension, obesity, smoking, and diabetes. The biggest cause of death at the age of 60 years is non-communicable diseases such as coronary heart disease, heart failure, hypertension, and stroke. Knowledge about daily care and adherence to treatment plays an important role in reducing morbidity and mortality in heart failure sufferers. Register data in the heart polyclinic and ICCU (Intensive Cardiac Care Unit) room at Tabanan District Hospital during 2020-2021 showed an increase in the number of re-hospitalizations for heart failure sufferers and a decrease in routine visits by heart failure sufferers to the polyclinic during the pandemic. Data from short interviews with heart failure sufferers and accompanying families or patient caretakers revealed a lack of knowledge about heart failure care and the importance of routine control. Partners caring for heart patients at Tabanan Hospital have never received training regarding heart disease and preventing the progression of heart disease and have experienced Difficulty in keeping family business bookkeeping to support the family economy. The PKM method is through training on heart disease, conselling, training on periodic body weight (BB) measurements, distribution of automatic weight measuring tools, and video playback which begins with a pre-test and ends with a post-test to measure the success/output of PKM which is carried out at the same time as World Heart Failure Awareness Day or World Heart Failure Day is May 3, 2022.